Transmembrane peptide 4 and 5 of APJ are essential for its heterodimerization with OX1R - Wan, Lei; Xu, Fangfang; Liu, Chang; Ji, Bingyuan; Zhang, Rumin; Wang, Peixiang; Wu, Fei; Pan, Yanyou; Yang, Chunqing; Wang, Chunmei; Chen, Jing (Biochemical and biophysical research communications, 2020)
Increasing evidence indicates some G protein-coupled receptors function as a heterodimer, which provide a novel target for therapeutics investigation. However, study on the receptor-receptor interaction interface, a potent target on interfering dimer formation, are still limited. Here, using bioluminescence resonance energy transfer (BRET) combined with co-immunoprecipitation (Co-IP), we found a new constitutive GPCR heterodimer, apelin receptor (APJ)-orexin receptor type 1 (OX1R). Both APJ and OX1R co-internalized when constantly subjected to cognate agonist (apelin-13 or orexin-A) specific to either protomer. Combined with BRET and immunostaining, the in vitro synthesized transmembrane peptides (TMs) interfering experiments suggests that TM4 and 5 of APJ act as the interaction interface of the APJ-OX1R heterodimer, and co-internalization could be disrupted by these peptides as well. Our study not only provide new evidence on GPCR heterodimerization, but address a novel heterodimerization interface, which can be severed as a potential pharmacological target. •APJ and OX1R could form a constitutive heterodimer.•Transmembrane peptides 4 and 5 serve as the interaction interface of the dimer.•Both protomers co-internalize when subject to agonist specific to either protomer.